Economic and health impacts of genetically modified eggplant: Results from a randomized controlled trial of Bt brinjal in Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Abedin, Naveen; Hossain, Nusrat Z. (International Food Policy Research Institute, 2019)
In this paper, we assess the impacts of genetically modified eggplant, Bt brinjal, on economic and health outcomes in Bangladesh using a cluster randomized controlled design. Bt brinjal cultivation reduces the cost of pesticide use by 47 percent. This is driven by reductions in the use of pesticides with adverse ecological impacts by 82 percent, and reductions in the use of pesticides with adverse effects on farmer health by 23 percent. Individuals who had a preexisting chronic condition consistent with pesticide exposure and who lived in villages randomly selected to grow Bt brinjal were 11.5 percentage points less likely to report a symptom of pesticide exposure and were 11 percentage points less likely to incur cash medical expenses to treat these symptoms. Net yields were 42 percent higher for Bt brinjal farmers, and our descriptive distributional work suggests that these yield gains are widespread. The differences in net yields were driven by two outcomes: the quantity harvested was higher on Bt brinjal fields, by 114 kilograms per farmer; and after harvesting, fewer fruits were discarded because of damage due to pests and diseases, by 40 kilograms per farmer. Increased production, together with a 14 percent increase in price and a 10 percent reduction in costs, leads to a substantial increase in profits from cultivating Bt brinjal for treatment farmers compared with conventional brinjal produced by control farmers. Bt brinjal is a publicly developed GMO that conveys significant health benefits, both human and ecological, while raising farmer incomes.